Zebrafish acid ceramidase: expression in Pichia pastoris GS115and biochemical characterization - Rajput, Vijay B.; Karthikeyan, Muthukumarasamy; Ramasamy, Sureshkumar (International Journal of Biological Macromolecules, 2019)
Acid ceramidase (N-acylsphingosine deacylase EC 3.5.1.23; AC) catalyzes the hydrolysis of ceramide into sphingosine (SPH) and free fatty acid. Zebrafish acid ceramidase (AC) has 60% homology with the human AC). Mutations in the human AC gene asah1 are known to cause Farber disease and spinal muscular atrophy with progressive myoclonic epilepsy. Zebrafish AC was overexpressed in Pichia pastoris by inserting asah1b gene into the genome. The majority of the overexpressed enzyme was secreted into the culture medium and purified to apparent homogeneity by stepwise chromatography. The recombinant protein was glycosylated precursor, that further undergoes limited autoproteolytic processing into two subunits (alpha and beta) which are visible in SDS-PAGE. The zebrafish AC is heterodimer associated with an inter-subunit disulfide bond. SDS-PAGE estimated the mass of native enzyme to be approximately 50 kDa & size exclusion chromatography estimated the mass of the active enzyme as approximately 100 kDa, suggesting the formation of a dimer of heterodimers. The protein was secreted as a mixture of processed and unprocessed forms in the culture media. A preliminary characterization of purified zebrafish AC was done by an enzyme assay. The zebrafish AC expressed in Pichia pastoris would be used for further structural and functional analysis. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Autoproteolytic processing; Pichia pastoris; Zebrafish acid ceramidase